Detecting Temporal Change in Dynamic Sounds: On the Role of Stimulus Duration, Speed, and Emotion - Schirmer, Annett; Escoffier, Nicolas; Cheng, Xiaoqin; Feng, Yenju; Penney, Trevor B. (Frontiers in Psychology, 2016)
For dynamic sounds, such as vocal expressions, duration often varies alongside speed. Compared to longer sounds, shorter sounds unfold more quickly. Here, we asked whether listeners implicitly use this confound when representing temporal regularities in their environment. In addition, we explored the role of emotions in this process. Using a mismatch negativity (MMN) paradigm, we asked participants to watch a silent movie while passively listening to a stream of task-irrelevant sounds. In Experiment 1, one surprised and one neutral vocalization were compressed and stretched to create stimuli of 378 and 600 ms duration. Stimuli were presented in four blocks, two of which used surprised and two of which used neutral expressions. In one surprised and one neutral block, short and long stimuli served as standards and deviants, respectively. In the other two blocks, the assignment of standards and deviants was reversed. We observed a climbing MMN-like negativity shortly after deviant onset, which suggests that listeners implicitly track sound speed and detect speed changes. Additionally, this MMN-like effect emerged earlier and was larger for long than short deviants, suggesting greater sensitivity to duration increments or slowing down than to decrements or speeding up. Last, deviance detection was facilitated in surprised relative to neutral blocks, indicating that emotion enhances temporal processing. Experiment 2 was comparable to Experiment 1 with the exception that sounds were spectrally rotated to remove vocal emotional content. This abolished the emotional processing benefit, but preserved the other effects. Together, these results provide insights into listener sensitivity to sound speed and raise the possibility that speed biases duration judgments implicitly in a feed-forward manner. Moreover, this bias may be amplified for duration increments relative to decrements and within an emotional relative to a neutral stimulus context.